Recent Advances in Thermo and Fluid Dynamics - Gorji-Bandpy, Mofid (IntechOpen, 2015)
Thermodynamics is a branch of physics concerned with heat and temperature and their relation to energy and work. It defines macroscopic variables, such as internal energy, entropy, and pressure, that partly describe a body of matter or radiation. It states that the behavior of these variables is subject to general constraints that are common to all materials, not to the peculiar properties of particular materials. These general constraints are expressed in the three laws of thermodynamics which had a deep influence on the development of physics and chemistry. The book aims to present novel ideas that are crossing traditional disciplinary boundaries and introducing a wide spectrum of viewpoints and approaches in applied thermodynamics of the third millennium. The book will be of interest to those working in the fields of propulsion systems, power generation systems, chemical industry, quantum systems, refrigeration, fluid flow, combustion, and other phenomena.